â€œ Analysis of Introduction Section Written by Lecturers on Lateralisasi Journal and Math-UMB Edu Journal â€œ - Epi Wadison; Mariyah Ulva (Teaching English and Language Learning English Journal, 2021)
The aim of this research was to know about introduction section written by Lecturers on Lateralisasi Journal and Math-UMB Edu Journal, the research found that the introduction section of Research article written by Lecturers on Lateralisasi journal and Math-UMB Edu journal were â€œnot sufficientâ€ because the Lecturers did not use all of moves in introduction section based on Swales (1990). The result, all Lecturers did not use Move II, Whereas, in writing a good and strong introduction section must had Move I, Move II, and Move III. Thus, the writer would like to suggest that the Lecturersâ€™ research articles in journal had understand about the concept of Rhetorical move based on Swales in introduction section Â Key Words : Rhetorical Move, Linguistics Feature, Introduction Section.